1996
DOI: 10.1111/j.1467-8268.1996.tb00090.x
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure and Technology Constraints to Agricultural Development in the Humid and Subhumid Tropics of Africa

Abstract: Green Rcvolution technologies havc not bccn widely adoptcd in Africa. What arc the chanccs that they will play a major rolc in thc ncar futurc? This paper shows that thc cnabling infrastructurc, espccially rural roads and irrigation systcms arc not likely to be in place in the humid and sub-humid tropics of Africa in thc next 20-30 ycars. Conscqucntly a typology of thc more appropriate set of technology that is input and infrastructurc cficicnt, has high returns to seasonal labor and is sustainable is prcsentc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 15 publications
1
16
0
3
Order By: Relevance
“…Spencer (1994) compared the density of Africa's road network in early 1990s with that of India in the 1950s prior to the green revolution and found that India had nearly six times the density on average. If one takes the Indian density as broadly indicative of what is needed for rapid agricultural growth, then it is clear that much of Africa will need massive investments in rural infrastructure before it can hope to launch a successful agricultural revolution (see also Platteau (1996)).…”
Section: (V) Property Rightsmentioning
confidence: 99%
“…Spencer (1994) compared the density of Africa's road network in early 1990s with that of India in the 1950s prior to the green revolution and found that India had nearly six times the density on average. If one takes the Indian density as broadly indicative of what is needed for rapid agricultural growth, then it is clear that much of Africa will need massive investments in rural infrastructure before it can hope to launch a successful agricultural revolution (see also Platteau (1996)).…”
Section: (V) Property Rightsmentioning
confidence: 99%
“…The precarious state of Africa's food security, the extent of the continent's rural poverty, and the failure of many conventional programs and projects to bring about meaningful progress 21 call for a rethinking of the continent's agricultural R&D strategy in the 21st century 6,7,9,14 . Although many different models of partnerships have promoted PPP in technology delivery, few have provided tangible results (improved farmers' livelihoods) in developing country agriculture.…”
Section: Resultsmentioning
confidence: 99%
“…Aside from climatic factors, other causes for the failure of a GR in SSA include the low availability of irrigation, insufficient fertilizer usage, soil degradation in some areas, under-developed infrastructure, poor governance and coordination, inaccessibility to markets, lack of agricultural credit and education (Kuyvenhoven, 2008;Hayami & Godo, 2005;Spencer, 1994;David & Otsuka, 1994).…”
Section: Notesmentioning
confidence: 99%